Identification of a chemical probe for bromo and extra C-terminal bromodomain inhibition through optimization of a fragment-derived hit. - Fish, P; Filippakopoulos, P; Bish, G; Brennan, P; Bunnage, M; Cook, A; Federov, O; Gerstenberger, B; Jones, H; Knapp, S; Marsden, B; Nocka, K; et al. (2012)
The posttranslational modification of chromatin through acetylation at selected histone lysine residues is governed by histone acetyltransferases (HATs) and histone deacetylases (HDACs). The significance of this subset of the epigenetic code is interrogated and interpreted by an acetyllysine-specific protein-protein interaction with bromodomain reader modules. Selective inhibition of the bromo and extra C-terminal domain (BET) family of bromodomains with a small molecule is feasible, and this may represent an opportunity for disease intervention through the recently disclosed antiproliferative and anti-inflammatory properties of such inhibitors. Herein, we describe the discovery and structure-activity relationship (SAR) of a novel, small-molecule chemical probe for BET family inhibition that was identified through the application of structure-based fragment assessment and optimization techniques. This has yielded a potent, selective compound with cell-based activity (PFI-1) that may further add to the understanding of BET family function within the bromodomains.